Model Pengendalian Faktor Risiko Kematian Neonatal di Kabupaten Sumba Timur - Masrida Sinaga; Keristina Br. Ginting (Universitas Nusa Cendana, 2019)
The Infant Mortality Rate (IMR) is still high in Indonesia, and the Province of East Nusa Tenggara (NTT Province) is one of the contributors to the high IMR, the highest in Sumba Timur Districts. Neonatal death can occur due to risk factors in the mother and also the child.The purpose of this study is to analyze the factors that influence neonatal mortality, so that the control model can be developed. The study used a case-control design, with the population being all newborns who were delivered at and recorded in care hospitals and health centers located in Sumba Timur Districts in 2016. Case samples were 116 cases of neonatal mortality, and controls were 232 neonatal lives who is the closest neighbour to a case with equitable socio-economic status. Data were analyzed descriptively and inferentially. Further research was conducted on 166 mothers with conditions during pregnancy and childbirth optimal health and children born also without risk factors. The most dominant risk factors affecting neonatal deaths in Sumba Timur districts are asphyxia in infants, complications of pregnancy/childbirth, maternal anemia, prematurity and LBW. From the compatibility test of the logistic regression model partially, the probability of p1 = 0.03 p0 is obtained. That is, if asphyxia in infants, complications of pregnancy, maternal anemia, prematurity and low birth weight can be overcome, then the risk of neonatal death is only 0.03 or 3%. The results of follow-up studies of 166 birth mothers in 2018 who at the time of pregnancy and childbirth without risk factors (without complications of pregnancy/childbirth, there is no anemia in the mother, without asphyxia cases in infants, not premature and not LBW), it turns out neonatal mortality is only 1 case (0.6%). This result is the basis for determining the model of control and prevention of risk factors for neonatal death, namely optimizing maternal health during pregnancy and during childbirth. Among other things by checking the pregnancy, good nutritional status, handling complications of pregnancy and childbirth optimally, and giving birth to workers and adequate health facilities.